COMPLEX NETWORK ANALYSIS OF GLOBAL STOCK INDEX FOR RENEWABLE-ENERGY INDUSTRY USING THE MINIMUM SPANNING TREE METHOD - Natalia, Anisa
Econophysics is a multidisciplinary science within the branch of complex systems physics that uses mathematical methods to analyze the phenomena of complex systems in the economy. This field has conducted many studies of stock market fluctuations. In today's global stock market, the renewable energy industry is one of the fastest-growing sectors. The study of the stock index network of the renewable energy industry will be presented in this final project. This study also analyzes the relationship between the form of the network topology and the growth rate of the stock index. The method used to analyze the complex network of global stock indexes for the renewable energy industry is the Minimum Spanning Tree (MST) approach. The results show that the shape of the network topology is in line with the growth rate of the renewable energy industry stock index. The use of the MST method results in an alignment between the network topology that is formed with the growth rate of the renewable energy industry stock index of 80%. Centrality analysis is also carried out to determine the form of the stock index network topology and to determine the most dominant and influential.